Silicon composite material and preparation method thereof, negative pole piece, battery and electric device

By using silicon composite materials in the electrode sheet, combining silicon-based materials and flexible materials, the problem of silicon-based materials crushing the current collector is solved, and the compaction density of the electrode sheet and the energy density of the battery are improved.

CN119581503AActive Publication Date: 2025-03-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311143407.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

Silicon-based materials tend to crush the current collector when preparing electrode sheets, limiting the compaction density of the electrode sheets and the energy density of the battery.

Method used

Silicon composite material is used, which consists of a silicon-based material and a flexible material whose hardness is less than that of a silicon-based material. The flexible material is located on part or all of the surface of the silicon-based material to buffer the pressure of the current collector.

Benefits of technology

Through the buffering effect of the flexible material, the risk of current collector being crushed is reduced, the compaction density of the electrode sheet is increased, and the energy density of the battery is increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581503A_ABST
    Figure CN119581503A_ABST
Patent Text Reader

Abstract

The invention provides a silicon composite material and a preparation method thereof, a negative pole piece, a battery and an electric device. The silicon composite material comprises a silicon-based material and a flexible material, and the hardness of the flexible material is smaller than that of the silicon-based material. The silicon-based material comprises at least one of monatomic silicon, a silicon-oxygen compound, a silicon-carbon compound, a silicon-nitrogen compound and a silicon alloy. The flexible material is located on at least part of the surface of the silicon-based material. Through cooperation of the flexible material and the silicon-based material, the risk that the current collector is crushed during preparation of the electrode plate can be reduced, the compaction density of the electrode plate is improved, and the energy density of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a silicon composite material and a preparation method thereof, a negative electrode sheet, a battery and an electrical device. Background Art

[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.

[0003] Silicon-based materials have a high gram capacity, and introducing them into secondary batteries may increase the energy density of the battery. However, silicon-based materials usually have a high hardness, which can easily damage the current collector when preparing the electrode plate, thus restricting the improvement of the compaction density of the electrode plate, and further restricting the further improvement of the battery energy density. Summary of the invention

[0004] In order to achieve the above-mentioned purpose, the present application provides a silicon composite material, including a silicon-based material and a flexible material, wherein the hardness of the flexible material is less than the hardness of the silicon-based material. The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The flexible material is located on at least part of the surface of the silicon-based material. In the above-mentioned silicon composite material, through the cooperation of the flexible material and the silicon-based material, the flexible material can buffer the force of the silicon-based material on the current collector, which can reduce the risk of the current collector being crushed when preparing the electrode pole piece, which is beneficial to improve the compaction density of the electrode pole piece, thereby improving the energy density of the battery.

[0005] In some embodiments, the flexible material includes a flexible conductive material. By introducing the flexible conductive material, the conductivity of the silicon composite material can be improved, thereby improving the electrical performance of the battery. Optionally, the flexible conductive material includes at least one of graphite and soft carbon.

[0006] In some embodiments, the Dv50 of the flexible material is ≤ the Dv50 of the silicon-based material. The flexible material can be more evenly dispersed on the surface of the silicon-based material, which is conducive to further improving the buffering effect of the flexible material on the silicon-based material.

[0007] In some embodiments, the Dv50 of the flexible material is 1 μm to 5 μm. The Dv50 of the flexible material within this range can make the flexible material more evenly dispersed on the surface of the silicon-based material, and at the same time can provide a more suitable deformation space between the flexible materials. The suitable deformation space is conducive to buffering the force between the silicon-based material and the current collector, and reducing the risk of damage to the current collector during the preparation of the electrode sheet.

[0008] In some embodiments, the Dv50 of the silicon-based material is 2 μm to 7 μm. The Dv50 of the silicon-based material within this range can enable the electrode plate to have a higher compaction density, which is beneficial to improving the energy density of the battery.

[0009] In some embodiments, the silicon-based material and the flexible material are both granular materials, and the flexible material is distributed in granular form on at least part of the surface of the silicon-based material. The flexible material is distributed in granular form to play a better buffering role. When the sphericity of the silicon-based material is low, that is, the silicon-based material has sharp protrusions, the flexible material distributed in granular form can better cooperate with the protrusions, reducing the risk of damage to the current collector caused by the protrusions. Optionally, the flexible material is distributed in granular form on the entire surface of the silicon-based material.

[0010] In some embodiments, the mass ratio of the flexible material to the silicon-based material is (1-9): 1. The mass ratio of the flexible material to the silicon-based material within this range can give full play to the buffering effect of the flexible material and reduce the risk of current collector damage. At the same time, the mass ratio of the flexible material to the silicon-based material within this range is conducive to improving the compaction density of the pole piece, thereby enabling the battery to maintain a higher energy density.

[0011] In some embodiments, the silicon-carbon composite includes a porous carbon material and elemental silicon located in the pores of the porous carbon material. The pores inside the porous carbon material can provide a certain reserved expansion space for elemental silicon, reduce the overall expansion of the silicon-carbon composite, and improve the structural stability of the electrode plate during charging and discharging.

[0012] In some embodiments, the specific surface area of ​​the porous carbon material is 500 m 2 / g~1800m 2 / g. The specific surface area of ​​porous carbon materials within this range can provide a larger space for the attachment of single-element silicon, thereby promoting the improvement of battery energy density.

[0013] In some embodiments, the pores of the porous carbon material have a pore size of 2 nm to 50 nm. The pore size of the porous carbon material within this range can provide a larger expansion space for the expansion of single silicon and enable the battery to have better cycle performance.

[0014] In some embodiments, the mass percentage of the elemental silicon in the silicon-carbon composite is 20% to 60%. When the mass percentage of the elemental silicon is within this range, the battery can have both high energy density and good cycle stability.

[0015] In some embodiments, the silicon composite material further includes a coating layer, the coating layer includes at least one of carbon and a metal oxide, and the coating layer completely or partially covers the silicon-based material and the flexible material. The coating layer can be provided to provide a certain barrier to the electrolyte, further reducing the risk of direct contact between the electrolyte and the silicon-based material, and reducing the side reactions between the electrolyte and the silicon-based material inside the battery, which is beneficial to improving the battery's cycle and fast charging performance. Optionally, the metal oxide includes at least one of aluminum oxide and titanium dioxide.

[0016] In some embodiments, the coating layer has a thickness of 5 nm to 60 nm. The coating layer thickness within this range can maintain a good coating effect while making the silicon composite material have a suitable particle size, which is beneficial to promoting the improvement of the compaction density of the electrode sheet.

[0017] In some embodiments, the Dv50 of the silicon composite material is 8 μm to 40 μm. The Dv50 of the silicon composite material within this range can provide a path of suitable size for the diffusion of lithium ions and improve the transport kinetics of lithium ions.

[0018] In some embodiments, the tap density of the silicon composite material is 0.9 g / cm 3 ~1.2g / cm 3 The tap density of the silicon composite material within this range is conducive to improving the compaction density of the negative electrode sheet.

[0019] In some embodiments, the specific surface area of ​​the silicon composite material is 0.8 m 2 / g~1.5m 2 / g. The specific surface area of ​​the silicon composite material within this range can enable the electrode plate to have good dynamic performance.

[0020] The present application also provides a method for preparing a silicon composite material, comprising the following steps: mixing a silicon-based material, a flexible material and a solvent to obtain a dispersion; the hardness of the flexible material is less than the hardness of the silicon-based material; the silicon-based material comprises at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, silicon-nitrogen compounds and silicon alloys. The dispersion is spray-dried.

[0021] In some embodiments, the solid content of the dispersion is 1% to 40%.

[0022] In some embodiments, the temperature of the hot air in the spray drying process is 150°C to 200°C.

[0023] In some embodiments, the flow rate of the hot air for the spray drying process is 0.08 m 3 / min~0.2m 3 / min.

[0024] The present application also provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector; the negative electrode film layer comprises the silicon composite material or the silicon composite material prepared by the preparation method.

[0025] In some embodiments, the compaction density of the negative electrode sheet is 1.3 g / cm 3 ~1.75g / cm 3 The compaction density of the negative electrode sheet within this range is beneficial to improving the energy density of the battery.

[0026] In some embodiments, the full charge expansion rate of the negative electrode plate is 22% to 50%. The full charge expansion rate within this range can make the battery have better cycle stability.

[0027] The present application also provides a secondary battery, comprising the negative electrode plate.

[0028] The present application also provides an electrical device, comprising the secondary battery mentioned above. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0030] Figure 1 It is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0031] Figure 2 for Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0032] Figure 3 FIG. 1 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0033] Figure 4 Schematic diagram of the structure of a silicon composite material in one embodiment of the present application.

[0034] Figure 5 This is a schematic structural diagram of a silicon composite material in another embodiment of the present application.

[0035] Description of reference numerals:

[0036] 1. Secondary battery; 11. Shell; 12. Electrode assembly; 13. Cover plate; 2. Electric device; 3. Silicon composite material; 31. Silicon-carbon composite material; 32. Graphite; 33. Coating layer.

[0037] In order to better describe and illustrate the embodiments and / or examples of the inventions disclosed herein, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered to limit the scope of the disclosed inventions, the embodiments and / or examples currently described, and any of the best modes of these inventions currently understood. DETAILED DESCRIPTION

[0038] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0040] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0042] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0043] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0045] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true or exists, and B is false or does not exist; A is false or does not exist, and B is true or exists; or both A and B are true, or both A and B exist.

[0046] Unless otherwise stated, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise stated, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art. For example, the test can be performed according to the method provided in the examples of this application.

[0047] An embodiment of the present application provides a silicon composite material. The silicon composite material includes a silicon-based material and a flexible material, and the hardness of the flexible material is less than the hardness of the silicon-based material. The silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The flexible material is located on at least a portion of the surface of the silicon-based material. In the silicon composite material, through the cooperation of the flexible material and the silicon-based material, the flexible material can buffer the force of the silicon-based material on the current collector, which can reduce the risk of the current collector being crushed when preparing the electrode pole piece, which is beneficial to improve the compaction density of the electrode pole piece, thereby increasing the energy density of the battery.

[0048] Optionally, the flexible material is located on the entire surface of the silicon-based material.

[0049] Furthermore, when the silicon composite material is applied to a secondary battery, the flexible material is located on at least part of the surface of the silicon-based material. The flexible material can reduce the risk of direct contact between the electrolyte and the silicon-based material, thereby reducing the side reactions between the electrolyte and the silicon-based material inside the battery, which is beneficial to improving the cycle performance of the battery.

[0050] In some embodiments, the flexible material includes a flexible conductive material. By introducing the flexible conductive material, the conductivity of the silicon composite material can be improved, thereby improving the electrical performance of the battery. Optionally, the conductive material includes at least one of graphite and soft carbon. It is understood that the graphite includes at least one of natural graphite and artificial graphite.

[0051] In some embodiments, the Dv50 of the flexible material is less than or equal to the Dv50 of the silicon-based material. In this case, the flexible material can be more evenly dispersed on the surface of the silicon-based material, which is conducive to further improving the buffering effect of the flexible material on the silicon-based material. Optionally, the Dv50 of the flexible material is less than the Dv50 of the silicon-based material.

[0052] It is understood that in this application, Dv50 refers to the particle size corresponding to when the cumulative particle size distribution number of particles reaches 50% in the volume cumulative distribution curve. Its physical meaning is that particles with a particle size smaller than (or larger than) it account for 50%. As an example, Dv50 can be obtained by referring to the GB / T 19077-2016 test method and using the particle size distribution curve obtained by the laser diffraction particle size distribution measuring instrument Mastersizer3000.

[0053] As some optional examples of Dv50 of flexible materials, Dv50 of flexible materials is 1μm to 5μm. Dv50 of flexible materials within this range can make the flexible materials more evenly dispersed on the surface of silicon-based materials, and at the same time can make the flexible materials have a more suitable deformation space. Suitable deformation space is conducive to buffering the force between silicon-based materials and current collectors, and reducing the risk of current collector damage during electrode sheet preparation. Optionally, Dv50 of flexible materials can be 1μm, 2μm, 3μm, 4μm, 5μm, etc.

[0054] As some optional examples of Dv50 of silicon-based materials, Dv50 of silicon-based materials is 2μm to 7μm. Dv50 of silicon-based materials within this range can be that the electrode plate has a higher compaction density, which is beneficial to improve the energy density of the battery. Optionally, Dv50 of silicon-based materials can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, etc.

[0055] It is understandable that the flexible material and the silicon-based material can be combined together by the surface tension between the flexible material and the silicon-based material. Optionally, the silicon composite material may further include a binder. The binder can further improve the bonding force between the flexible material and the silicon-based material, so that the flexible material and the silicon-based material are better combined together, which is conducive to further improving the structural stability of the silicon composite material. Optionally, the binder can be at least one of polyvinyl pyrrolidone, polyethylene glycol and sodium carboxymethyl cellulose.

[0056] In some embodiments, the silicon-based material and the flexible material are both granular materials, and the flexible material is distributed in granular form on at least part of the surface of the silicon-based material. The flexible material is distributed in granular form to play a better buffering role. When the sphericity of the silicon-based material is low, that is, the silicon-based material has sharp protrusions, the flexible material distributed in granular form can better cooperate with the protrusions, reducing the risk of damage to the current collector caused by the protrusions. Optionally, the flexible material is distributed in granular form on the entire surface of the silicon-based material.

[0057] In some embodiments, the mass ratio of the flexible material to the silicon-based material is (1-9):1. The mass ratio of the flexible material to the silicon-based material within this range can give full play to the buffering effect of the flexible material and reduce the risk of current collector damage. At the same time, the mass ratio of the flexible material to the silicon-based material within this range can keep the battery at a high energy density. Optionally, the mass ratio of the flexible material to the silicon-based material can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, etc.

[0058] In some embodiments, the silicon oxide compound comprises a chemical formula of SiO x wherein 0<x<2. Further optionally, 0.5≤x≤1.5. Further optionally, the silicon oxide compound comprises SiO.

[0059] Further optionally, metal elements may be distributed on the surface of the silicon oxide compound and / or inside the silicon oxide compound to reduce the proportion of irreversible phases (e.g., SiO2) and improve the efficiency of the active material. The metal may be at least one selected from Li, Mg, and Al. The introduction of these metal elements may reduce the risk of damage to the silicon oxide compound and improve the life of the silicon oxide compound. Alternatively, the metal may be at least one of Li and Mg. In terms of mass percentage of the silicon oxide compound, the mass percentage of the metal element may be 0.1% to 25%, and optionally 3% to 15%.

[0060] Optionally, the silicon nitrogen compound includes Si3N4.

[0061] In some embodiments, the silicon-carbon composite includes a porous carbon material and elemental silicon located in the pores of the porous carbon material. The pores inside the porous carbon material can provide a certain reserved expansion space for the elemental silicon, reduce the overall expansion of the silicon-carbon composite, and improve the structural stability of the electrode plate during charging and discharging. Optionally, the elemental silicon includes nano-silicon.

[0062] Silicon-carbon composites usually have a harder texture. When applied to electrode plates, the harder silicon-carbon composites may cause certain damage to the current collector during the cold pressing process, thereby adversely affecting the performance of the electrode plates and the battery. In the present application, by combining a flexible material with the silicon-carbon composite, the flexible material is softer than the silicon-carbon composite, which can disperse the stress caused by the silicon-carbon composite during the cold pressing process, reduce the adverse effects of the silicon-carbon composite on the current collector during the cold pressing process, and thus improve the structural stability of the electrode plates, thereby improving the performance of the battery.

[0063] Furthermore, the pressure bearing capacity of the silicon-carbon composite is poor and it is easy to break during the cold pressing process. In the present application, by combining the flexible material with the silicon-carbon composite, the silicon composite material can have a better pressure bearing capacity. When the silicon composite material is introduced into the electrode plate, it is beneficial to further improve the compaction density of the electrode plate.

[0064] In some embodiments, the specific surface area of ​​the porous carbon material is 500 m 2 / g~1800m 2 / g. The specific surface area of ​​the porous carbon material within this range can provide a larger space for the attachment of single-element silicon, thereby promoting the improvement of battery energy density. Optionally, the specific surface area of ​​the porous carbon material can be 500m 2 / g、600m 2 / g、700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g, etc.

[0065] In some embodiments, the pores of the porous carbon material have a pore size of 2 nm to 50 nm. The pore size of the porous carbon material within this range can provide a larger expansion space for the expansion of elemental silicon, while allowing the battery to have better cycle performance and storage performance. Optionally, the pores of the porous carbon material are mesopores.

[0066] In some embodiments, the mass percentage of elemental silicon in the silicon-carbon composite is 20% to 60%. The mass percentage of elemental silicon in this range can be a battery with both high energy density and good cycle stability. Optionally, the mass percentage of elemental silicon in the silicon-carbon composite can be 20%, 30%, 40%, 50%, 60%, etc.

[0067] In some embodiments, the flexible material comprises graphite and the silicon-based material comprises a silicon-carbon composite. Figure 4 , which shows a schematic structural diagram of a silicon composite material in one embodiment of the present application. Figure 4 The corresponding silicon composite material 3 includes a silicon-carbon composite 31 and graphite 32, wherein the graphite 32 is located on at least a portion of the surface of the silicon-carbon composite 31. Figure 4 In the figure, the positional relationship between the silicon composite material 3, the silicon-carbon composite 31 and the graphite 32 is schematically shown, which does not mean that the actual shapes of the silicon composite material 3, the silicon-carbon composite 31 and the graphite 32 are Figure 4 In the silicon composite material, the shapes of the silicon composite material, the silicon-carbon composite and the graphite can be other shapes. For example, the shapes of the silicon composite material, the silicon-carbon composite and the graphite can be independently selected from at least one of a sphere and a spherical shape.

[0068] In some embodiments, the silicon composite material further includes a coating layer, the coating layer includes at least one of carbon and metal oxide, and the coating layer completely or partially covers the silicon-based material and the flexible material. The coating layer can be provided to provide a certain barrier to the electrolyte, further reducing the risk of direct contact between the electrolyte and the silicon-based material, reducing the side reactions between the electrolyte and the silicon-based material inside the battery, and helping to improve the battery's cycle and fast charging performance. Optionally, the coating layer can be a carbon coating layer.

[0069] See also Figure 5 , which shows a schematic structural diagram of a silicon composite material in another embodiment of the present application. Figure 5 The corresponding silicon composite material 3 includes a silicon-carbon composite 31 and graphite 32, wherein the graphite 32 is located on at least a portion of the surface of the silicon-carbon composite 31. The silicon composite material 3 also includes a coating layer 33. The coating layer 33 completely coats the silicon-carbon composite 31 and the graphite 32.

[0070] In some embodiments, the metal oxide includes at least one of aluminum oxide and titanium dioxide.

[0071] In some embodiments, the coating layer has a thickness of 5 nm to 60 nm. The coating layer thickness within this range can maintain a good coating effect while making the silicon composite material have a suitable particle size, which is conducive to promoting the improvement of the compaction density of the electrode sheet. Optionally, the coating layer thickness can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, etc.

[0072] It is understandable that the flexible material, silicon-carbon composite and coating layer in the silicon composite material can be detected and distinguished by transmission electron microscopy (TEM) and X-ray diffraction (XRD).

[0073] In some embodiments, the Dv50 of the silicon composite material is 8 μm to 40 μm. The Dv50 of the silicon composite material within this range can provide a path of appropriate size for the diffusion of lithium ions and improve the transport kinetics of lithium ions. Alternatively, the Dv50 of the silicon composite material can be 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc.

[0074] In some embodiments, the tap density of the silicon composite material is 0.9 g / cm 3 ~1.2g / cm 3 The tap density of the silicon composite material within this range is conducive to improving the compaction density of the negative electrode sheet. Optionally, the tap density of the silicon composite material is 0.9 g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 Etc. It is understood that the tap density of the silicon composite material can be measured by a tap density meter. The graduated cylinder containing the silicon composite material is fixed on a mechanical vibration device, and the vibration motor drives the mechanical vibration device to vibrate vertically up and down, and the graduated cylinder containing the silicon composite material vibrates rhythmically with the mechanical vibration device. As the number of vibrations increases, the silicon composite material in the graduated cylinder is gradually vibrated. After the number of vibrations reaches the set number, the mechanical vibration device stops vibrating, and the volume of the graduated cylinder is read. According to the definition of density: mass divided by volume, the tap density of the silicon composite material is calculated.

[0075] In some embodiments, the specific surface area of ​​the silicon composite material is 0.8 m 2 / g~1.5m 2 / g. The specific surface area of ​​the silicon composite material within this range can make the electrode plate have good dynamic performance. Optionally, the specific surface area of ​​the silicon composite material is 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, etc.

[0076] In some embodiments, the silicon composite material is in the form of spherical particles.

[0077] Another embodiment of the present application provides a method for preparing a silicon composite material. The method for preparing the silicon composite material comprises the following steps: mixing a silicon-based material, a flexible material and a solvent to obtain a dispersion; the hardness of the flexible material is less than the hardness of the silicon-based material; the silicon-based material comprises at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The dispersion is spray-dried. The preparation method is simple and easy, and the silicon composite material can be obtained by a spray-drying granulation method.

[0078] Optionally, spray drying is carried out in a dry hot air atmosphere. It is understood that during spray drying, the dispersion is placed in a hot air atmosphere for drying.

[0079] In some embodiments, the temperature of the hot air in the spray drying process is 150° C. to 200° C. Alternatively, the temperature of the hot air in the spray drying process may be 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., etc.

[0080] In some embodiments, the flow rate of hot air for spray drying is 0.08 m 3 / min~0.2m 3 / min. Optionally, the flow rate of hot air for spray drying is 0.08m 3 / min, 0.09m 3 / min、0.1m 3 / min, 0.11m 3 / min, 0.12m 3 / min, 0.13m 3 / min, 0.14m 3 / min, 0.15m 3 / min, 0.16m 3 / min, 0.17m 3 / min, 0.18m 3 / min, 0.19m 3 / min、0.2m 3 / min, etc.

[0081] In some embodiments, the solid content of the dispersion is 1% to 40%. Optionally, the solid content of the dispersion is 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc.

[0082] In some embodiments, the solvent comprises water.

[0083] In some embodiments, the preparation method of the silicon composite material includes the following steps: mixing the silicon-based material, the flexible material, the dispersant and the solvent to obtain a dispersion; and spray drying the dispersion. The addition of the dispersant can improve the dispersion effect of the silicon-based material and the flexible material in the solvent, which is conducive to improving the uniformity of the silicon composite material.

[0084] Optionally, the ratio of the total mass of the silicon-based material and the flexible material to the mass of the dispersant is (70-95): (5-30). Further optionally, the ratio of the total mass of the silicon-based material and the flexible material to the mass of the dispersant can be 70:30, 75:25, 80:20, 85:15, 90:10, 95:5, etc. Further optionally, the dispersant includes one or more of polyvinyl pyrrolidone, polyethylene glycol and sodium carboxymethyl cellulose.

[0085] In some embodiments, the preparation method of the silicon composite material includes the following steps: mixing the silicon-based material, the flexible material, the dispersant, the binder and the solvent to obtain a dispersion; and spray drying the dispersion. The addition of the binder can improve the bonding performance between the silicon-carbon composite and the graphite, making the structure of the obtained silicon composite material more stable.

[0086] Optionally, the binder includes one or more of polyvinyl pyrrolidone, polyethylene glycol and sodium carboxymethyl cellulose.

[0087] It is understood that the dispersion can be spray-dried using a spray dryer.

[0088] In some embodiments, the spray drying process further comprises: coating the solid material obtained by the spray drying process.

[0089] In some embodiments, after the spray drying process, the method further includes: performing a carbon coating process on the solid material obtained by the spray drying process in a gaseous carbon source atmosphere. The carbon coating process can improve the conductivity and fast charging performance of the silicon composite material.

[0090] Optionally, the carbon coating treatment includes the following steps: placing the solid material obtained by the spray drying treatment in a porcelain boat, and then placing the porcelain boat in a tubular furnace with Ar gas as the protective gas, heating the temperature to 600°C to 800°C at a heating rate of 2°C to 10°C, and keeping the temperature for 1h to 4h. Then, the Ar gas is replaced with a gaseous carbon source for 15min to 30min, and then cooled to room temperature. Further optionally, the gaseous carbon source includes at least one of CH4 and C2H2.

[0091] Another embodiment of the present application provides a negative electrode plate. The negative electrode plate includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector. The negative electrode film layer includes the above silicon composite material or the silicon composite material prepared by the above silicon composite material preparation method.

[0092] In some embodiments, the compaction density of the negative electrode sheet is 1.3 g / cm 3 ~1.75g / cm 3 The compaction density of the negative electrode sheet within this range is beneficial to improving the energy density of the battery. For example, the compaction density of the negative electrode sheet can be 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 wait.

[0093] In one embodiment, the full charge expansion rate of the negative electrode sheet is 22% to 50%. The full charge expansion rate within this range can make the battery have good cycle stability. Optionally, the full charge expansion rate of the negative electrode sheet can be 25%, 30%, 35%, 40%, 45%, etc. It is understandable that the full charge expansion rate of the negative electrode sheet can be measured as follows: The full charge expansion rate can be tested by the following method: Measure the original thickness of the negative electrode sheet, recorded as W0. Then disassemble the assembled battery after full charge, and measure the thickness of the negative electrode sheet after full charge, recorded as W1. Expansion rate α = (W1-W0) / W0. .

[0094] Another embodiment of the present application provides a secondary battery. The secondary battery includes the above-mentioned negative electrode plate.

[0095] Another embodiment of the present application provides an electric device, which includes the secondary battery mentioned above.

[0096] The secondary battery and the electric device of the present application will be described below with reference to the drawings as appropriate.

[0097] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0098] Positive electrode

[0099] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0100] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0101] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate. Optionally, the metal material may include but is not limited to one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Optionally, the polymer material substrate may include but is not limited to one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0102] As an example, the positive electrode active material may include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Optionally, lithium cobalt oxide includes LiCoO2. Lithium nickel oxide includes LiNiO2. Lithium manganese oxide includes at least one of LiMnO2 and LiMn2O4. Lithium nickel cobalt manganese oxide includes LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2(NCM333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 ) and LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 ) at least one of the following. Lithium nickel cobalt aluminum oxide includes LiNi 0.85 Co 0.15 Al 0.05 O2. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon. Optionally, the lithium iron phosphate includes LiFePO4 (LFP). The lithium manganese phosphate includes LiMnPO4. The weight ratio of the positive electrode active material in the positive electrode film layer is 80 to 100 weight %, based on the total weight of the positive electrode film layer.

[0103] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0 to 20 weight%, based on the total weight of the positive electrode film layer.

[0104] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0 to 20 weight %, based on the total weight of the positive electrode film layer.

[0105] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a positive electrode slurry. Optionally, the solvent includes N-methylpyrrolidone. The positive electrode slurry has a solid content of 40 to 80 wt%, and the viscosity at room temperature is adjusted to 5000 to 25000 mPa·s. The positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, it is cold-pressed by a cold rolling mill to form a positive electrode sheet; the positive electrode powder coating unit surface density is 15-35 mg / cm 2 The compaction density of the positive electrode is 3.0-3.6g / cm 3 , optional: 3.4-3.6g / cm 3 The calculation formula of the compaction density is: compaction density = coating surface density / (thickness of the electrode sheet after extrusion - thickness of the current collector).

[0106] It is understandable that the positive electrode sheet in the embodiment of the present application can be made by using the above-mentioned positive electrode sheet as the positive electrode sheet body and forming a solid electrolyte interface film on the surface of the positive electrode sheet body.

[0107] Negative electrode

[0108] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0109] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0110] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Optionally, the metal material includes at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0111] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include the silicon composite material in the embodiment of the present application. The negative electrode active material may also include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based material and lithium titanate, etc. The tin-based material may be selected from at least one of elemental tin, tin oxide and tin alloy. However, the negative electrode active material is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70 to 100 weight%, based on the total weight of the negative electrode film layer.

[0112] As natural graphite, unprocessed natural graphite such as flake graphite, stamped graphite, and earthy graphite or spherical natural graphite can be used. Flake graphite and stamped graphite show almost complete crystals, while earthy graphite has a low degree of crystallinity. In consideration of the electrode capacity, flake graphite and stamped graphite with high crystallinity can be used. For example, flake graphite can be spheroidized and used. In the case of spheroidized natural graphite, the particle size can be 5 to 30 μm, preferably 10 to 25 μm.

[0113] Artificial graphite can be generally produced by graphitization, which involves sintering raw materials such as coal tar, coal tar pitch, and petroleum heavy oil at 2500°C or above. After such graphitization, the raw materials are crushed to form secondary particles. These particles can also be used as negative electrode active materials after adjustment.

[0114] Generally speaking, the crystals of artificial graphite are randomly distributed within the particles, and have lower sphericity and sharper shapes than natural graphite. Artificial graphite can be in the form of powder, flake, block, plate or rod, but it is preferred that the orientation of the grains is isotropic to shorten the movement distance of lithium ions to improve output characteristics. Artificial graphite can be in the form of flakes and / or plates.

[0115] Artificial graphite includes commercially widely used mesophase carbon microbeads (MCMB), mesophase pitch-based carbon fibers (MPCF), block graphitized artificial graphite, powdered graphitized artificial graphite, graphite, etc. In addition, the particle size of the artificial graphite can be 5 to 30 μm, preferably 10 to 25 μm.

[0116] The specific surface area of ​​artificial graphite can be measured by the Brunauer-Emmett-Teller (BET) method. For example, using a porosity analyzer (Bell Japan Inc, Belsorp-II mini), it can be measured by the BET 6-point method by a nitrogen adsorption flow method. The same is true for the measurement of the specific surface area of ​​natural graphite described below.

[0117] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0 to 30% by weight, based on the total weight of the negative electrode film layer.

[0118] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0 to 20 weight %, based on the total weight of the negative electrode film layer.

[0119] In some embodiments, the negative electrode film layer may further include other additives, such as thickeners, etc. The weight ratio of the other additives in the negative electrode film layer is 0 to 15 weight %, based on the total weight of the negative electrode film layer. Optionally, the thickener includes sodium carboxymethyl cellulose (CMC-Na).

[0120] In some embodiments, the negative electrode film layer may be a single layer or multiple layers. When the negative electrode film layer is multiple layers, the active materials of any two layers may be the same or different.

[0121] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent to form a negative electrode slurry. Optionally, the solvent includes deionized water. The solid content of the negative electrode slurry is 30-70wt%, and the viscosity at room temperature is adjusted to 2000-10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after drying and cold pressing, the negative electrode sheet is obtained. The negative electrode powder coating unit surface density is 75-220mg / m 2 , the compaction density of negative electrode is 1.2~2.0g / m 3 .

[0122] It can be understood that the negative electrode plate in the embodiment of the present application can be made by using the above-mentioned negative electrode plate as the negative electrode plate body and forming a solid electrolyte interface film on the surface of the negative electrode plate body.

[0123] Electrolytes

[0124] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0125] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0126] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is generally 0.5 to 5 mol / L.

[0127] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0128] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0129] Isolation film

[0130] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0131] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0132] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0133] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0134] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate. The present application has no particular restrictions on the shape of the secondary battery, which can be cylindrical, square, or any other shape. For example, Figure 1 The secondary battery 1 is a square structure as an example.

[0135] In some embodiments, reference Figure 2 , the outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, and those skilled in the art can select according to specific actual needs.

[0136] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0137] As the electrical device, a secondary battery can be selected according to its usage requirements.

[0138] Figure 3 The power consumption device 2 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0139] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0140] Example

[0141] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0142] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0143] Example 1

[0144] The preparation method of the silicon composite material in this embodiment includes:

[0145] The silicon-based material silicon-carbon composite and the flexible material graphite are added to deionized water, stirred and dispersed evenly to obtain a dispersion. The dispersion is spray-dried using a spray dryer. The solid material obtained by the spray drying process is subjected to carbon coating in a gaseous carbon source atmosphere to obtain the silicon composite material in this embodiment.

[0146] Example 2 to Example 17

[0147] Compared with Example 1, the difference between Examples 2 to 17 is that the composition of the silicon composite material is different, as shown in Table 1.

[0148] Embodiment 18

[0149] Compared with Example 1, the difference of this example is that graphite is replaced by soft carbon.

[0150] Embodiment 19

[0151] Compared with Example 1, the difference of this example is that the silicon-carbon composite is replaced by a silicon-oxygen compound, wherein the mass percentage of silicon in the silicon-oxygen compound is 50%.

[0152] Embodiment 20

[0153] Compared with Example 1, the difference of this example is that the silicon-carbon composite is replaced by a silicon-nitrogen compound, wherein the mass percentage of silicon in the silicon-nitrogen compound is 50%.

[0154] The preparation method of the secondary battery is as follows:

[0155] (1) Preparation of positive electrode sheet.

[0156] The positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 97:2:1 and added to a solvent N-methylpyrrolidone (NMP) to make a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, dried at 85°C and cold pressed, and then die-cut and striped to make positive electrode sheets.

[0157] (2) Preparation of negative electrode sheets.

[0158] The negative electrode active material, conductive agent acetylene black, thickener sodium hydroxymethyl cellulose, and binder styrene butadiene rubber are added to the solvent water in a mass ratio of 96:2:1:1 and mixed evenly to form a negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried at 85°C, and then cold pressed at a pressure of 40 tons, wherein the cold pressing is performed using a cylindrical cold pressing roller, the cold pressing speed is 20m / min, and the temperature is 25°C to form a negative electrode sheet.

[0159] The negative electrode active material in the embodiment is the silicon composite material in the corresponding embodiment.

[0160] In Comparative Example 1, the negative electrode active material is a silicon-carbon composite.

[0161] In Comparative Example 2, the negative electrode active material is graphite.

[0162] (3) Preparation of isolation membrane.

[0163] A polyethylene microporous film is used as a porous isolation membrane substrate, and inorganic alumina powder, polyvinylpyrrolidone and acetone solvent are evenly mixed in a weight ratio of 3:1.5:5.5 to form a slurry, which is then coated on one side of the substrate and dried to obtain an isolation membrane.

[0164] (4) Preparation of electrolyte.

[0165] LiPF6 lithium salt is dissolved in a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:2:1), and fluoroethylene carbonate (FEC) additive is added to obtain an electrolyte. The concentration of LiPF6 in the electrolyte is 1 mol / L, and the mass percentage of FEC is 5wt%.

[0166] (5) Preparation of secondary batteries.

[0167] The positive electrode sheet, the positive electrode sheet and the isolation film are wound to obtain a bare battery cell, which is then packaged, injected, formed, vented and other processes to obtain the corresponding secondary battery.

[0168] Test example:

[0169] (1) The structural stability of the negative electrode sheets in the embodiments and comparative examples was tested.

[0170] a: The vertical cross-sections of the negative electrode sheets in the embodiments and comparative examples were observed using a SEM electron scanning electron microscope to measure the depth H of the active material embedded in the current collector, and the measurement results are shown in Table 1. H can be used to indicate the degree of damage to the negative electrode current collector, and a larger H value indicates more serious damage to the negative electrode current collector.

[0171] b: The negative electrode plates in the embodiments and comparative examples were tested for elongation at break. Take the cold-pressed negative electrode plates, and use a die-cutting knife to punch out samples into 50mm*15mm strips, where the 50mm direction is the processing direction of the plate, that is, the direction of movement of the plate relative to the cold-pressing roller. Use a high-speed rail tensile testing machine to carry out the tensile test. The two ends of the tensile machine need to be tightly attached with wrinkle glue to prevent the plate from loosening and falling off during stretching. The sample should be kept vertical and straight during stretching. The sample needs to break somewhere in the middle, and the data of fractures at both ends of the fixture will be discarded. The stretching speed is 2mm / min. The initial length of the negative electrode plate is L0, i.e. 50mm. The length when it is stretched and broken in the length direction is L1, and the elongation at break λ=(L1-L0) / L0. The test results are shown in Table 1.

[0172] (2) The volume energy density (VED) of the secondary battery in the embodiment and the comparative example was tested. The battery was left at a constant temperature of 25°C for 2 hours, then charged to 4.2V at 0.33C at 2.8V-4.2V, then charged at a constant voltage at 4.2V to a current ≤0.05C, left at rest for 10 minutes, and then discharged to 2.8V at 0.33C, and the capacity C0 of the battery was recorded. VED is the ratio of C0 to the volume of the battery shell. The test results are shown in Table 1.

[0173] (3) The cycle performance of the secondary battery in the embodiment and the comparative example was tested. The test method is: at 25°C, the battery to be tested was continuously charged and discharged at 0.5C in the range of 0-100% SOC, and each charge and discharge was left to stand for 30 minutes. The battery cycled to 300 cycles, and the discharge capacity of the nth cycle was recorded as C n The first cycle discharge capacity is recorded as C1, and the capacity retention rate of the nth cycle = (C n / C1)×100%, where the capacity retention rate after 300 cycles at 25℃=(C 300 / C1)×100. The test results are shown in Table 1.

[0174] Table 1

[0175]

[0176]

[0177] In Table 1, BET represents the specific surface area of ​​porous carbon materials, with the unit of m 2 / g. The pore size indicates the pore size of the porous carbon material, and the unit is nm. The percentage of silicon indicates the mass percentage of silicon in the silicon-based material. The unit of Dv50 of silicon-based material is μm. The unit of Dv50 of graphite is μm. Graphite: silicon-based material indicates the mass ratio of graphite to silicon-based material. The unit of carbon coating thickness is nm. The unit of Dv50 of silicon composite material is μm. The unit of tap density of silicon composite material is g / cm 3 The unit of specific surface area of ​​silicon composite material is m 2 / g. The unit of compaction density of negative electrode is g / cm 3 The embedding depth indicates the depth of the active material embedded in the current collector, and the unit is μm. The unit of volume energy density of secondary batteries is W·h / L.

[0178] In Table 1, it can be seen from the comparison between Example 1 and Comparative Example 1 that, compared with the silicon-carbon composite as the negative electrode active material, when the negative electrode active material includes the silicon-carbon composite and graphite, the damage to the negative electrode collector is smaller when preparing the negative electrode plate, and the volume energy density of the battery is higher.

[0179] It can be seen from the comparison between Example 1 and Comparative Example 2 that, compared with graphite as the negative electrode active material, when the negative electrode active material includes the silicon-carbon composite and graphite, the volume energy density of the battery is higher.

[0180] It can be seen from the comparison between Example 1 and Example 7 that when the Dv50 of the silicon-carbon composite in Example 7 is less than the Dv50 of graphite, the negative electrode current collector has certain damage and the cycle performance is low.

[0181] It can be seen from the comparison between Example 1, Example 8 and Example 9 that when the Dv50 of the silicon-carbon composite is larger or the Dv50 of graphite is smaller, the damage to the negative electrode current collector is greater when preparing the negative electrode sheet.

[0182] It can be seen from the comparison between Example 1 and Example 14 that the corresponding cycle performance of the battery in Example 14 is lower. The possible reason is that the specific surface area of ​​the silicon-carbon composite is larger, and the excessive pores lead to aggravated side reactions, which reduces the cycle performance of the battery. In addition, the specific surface area of ​​the silicon-carbon composite in Example 14 is larger, and the corresponding compaction density is smaller, and the volume energy density of the battery is smaller.

[0183] It can be seen from the comparison between Example 1 and Example 15 that the corresponding cycle performance of the battery in Example 15 is lower. The possible reason is that the specific surface area of ​​the silicon-carbon composite is small, part of the elemental silicon is located on the particle surface of the silicon-carbon composite, and the activity of elemental silicon is relatively high, which may deteriorate the cycle performance to a certain extent.

[0184] It can be seen from the comparison between Example 1 and Example 16 that when the pore size of the porous carbon in the silicon-carbon composite is larger, the compaction density is smaller and the volume energy density of the battery is smaller.

[0185] It can be seen from the comparison between Example 1 and Example 17 that when the thickness of the carbon coating layer is larger, the cycle performance of the battery is lower.

[0186] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0187] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A silicon composite material, characterized in that: It comprises a silicon-based material and a flexible material, wherein the hardness of the flexible material is less than that of the silicon-based material; the silicon-based material comprises at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, silicon-nitrogen compounds and silicon alloys; and the flexible material is located on at least a portion of the surface of the silicon-based material.

2. The silicon composite material according to claim 1, characterized in that: The flexible material comprises a flexible conductive material; Optionally, the flexible conductive material includes at least one of graphite and soft carbon.

3. The silicon composite material according to claim 1 or 2, characterized in that: The Dv50 of the flexible material is ≤ the Dv50 of the silicon-based material; Optionally, the Dv50 of the flexible material is 1 μm to 5 μm; Optionally, the Dv50 of the silicon-based material is 2 μm to 7 μm.

4. The silicon composite material according to any one of claims 1 to 3, characterized in that The silicon-based material and the flexible material are both granular materials, and the flexible material is distributed in granular form on at least a portion of the surface of the silicon-based material.

5. The silicon composite material according to any one of claims 1 to 4, characterized in that: The mass ratio of the flexible material to the silicon-based material is (1-9):

1.

6. The silicon composite material according to any one of claims 1 to 5, characterized in that The silicon-carbon composite comprises a porous carbon material and elemental silicon located in the pores of the porous carbon material; Optionally, the specific surface area of ​​the porous carbon material is 500 m 2 / g~1800m 2 / g; Optionally, the pores of the porous carbon material have a pore size of 2 nm to 50 nm; Optionally, the mass percentage of the elemental silicon in the silicon-carbon composite is 20% to 60%.

7. The silicon composite material according to any one of claims 1 to 6, characterized in that: The silicon composite material further comprises a coating layer, the coating layer comprises at least one of carbon and metal oxide, and the coating layer completely or partially covers the silicon-based material and the flexible material; Optionally, the metal oxide includes at least one of aluminum oxide and titanium dioxide; Optionally, the coating layer has a thickness of 5 nm to 60 nm.

8. The silicon composite material according to any one of claims 1 to 7, characterized in that: The Dv50 of the silicon composite material is 8 μm to 40 μm; and / or, The tap density of the silicon composite material is 0.9 g / cm 3 ~1.2g / cm 3 and / or, The specific surface area of ​​the silicon composite material is 0.8 m 2 / g~1.5m 2 / g.

9. A method for preparing a silicon composite material, characterized in that: The steps include: A silicon-based material, a flexible material and a solvent are mixed to obtain a dispersion; the hardness of the flexible material is less than the hardness of the silicon-based material; the silicon-based material comprises at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon compounds, silicon-nitrogen compounds and silicon alloys; The dispersion is spray dried.

10. The method for preparing the silicon composite material according to claim 9, characterized in that: The solid content of the dispersion is 1% to 40%; and / or, The temperature of the hot air in the spray drying process is 150°C to 200°C; and / or, The flow rate of the hot air in the spray drying process is 0.08m 3 / min~0.2m 3 / min.

11. A negative electrode plate, characterized in that: It comprises a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector; the negative electrode film layer comprises the silicon composite material according to any one of claims 1 to 8 or the silicon composite material prepared by the preparation method according to any one of claims 8 to 9.

12. The negative electrode sheet according to claim 11, characterized in that: The compaction density of the negative electrode sheet is 1.3 g / cm 3 ~1.75g / cm 3 and / or, The full charge expansion rate of the negative electrode plate is 22% to 50%.

13. A secondary battery, characterized in that: The invention comprises the negative electrode sheet according to any one of claims 11 to 12.

14. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 13.

Citation Information

Patent Citations

  • Silicon monoxide composite negative electrode material, preparation method thereof and lithium ion battery

    CN111082006A

  • Silicon-based composite negative electrode material and preparation method thereof, as well as negative electrode and preparation method thereof

    CN112768674A

  • Silicon-carbon composite particles, negative electrode active material, and negative electrode, electrochemical device, and electronic device comprising same

    CN114026713A

  • Negative electrode material as well as negative electrode plate and battery comprising negative electrode material

    CN115863574A

  • Long-circulation lithium battery negative electrode material as well as preparation method and application thereof

    CN116072831A

Cited By

  • Silicon composite material and preparation method, negative electrode sheet, battery, and electric device

    EP4654295A1